1999
DOI: 10.1038/sj.jp.7200191
|View full text |Cite
|
Sign up to set email alerts
|

Group B Streptococcus: To Culture or Not to Culture?

Abstract: Despite universal GBS culturing and very liberal use of antibiotics in labor, we were unable to effect a statistically significant change in the rate of early-onset GBS sepsis or mortality, and there was only a slightly decreased chorioamnionitis rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 12 publications
1
7
0
Order By: Relevance
“…Due to methodologic differences among studies, these authors declined to perform a meta-analysis of the studies they surveyed. 18 Katz et al, 19 in a more recent study, showed that despite a significant increase in the use of maternal antibiotics during labor, there was no change in the rate of EOGBS sepsis at their institution. However, only about half of their study patients was screened and received prophylaxis appropriately.…”
Section: Discussionmentioning
confidence: 99%
“…Due to methodologic differences among studies, these authors declined to perform a meta-analysis of the studies they surveyed. 18 Katz et al, 19 in a more recent study, showed that despite a significant increase in the use of maternal antibiotics during labor, there was no change in the rate of EOGBS sepsis at their institution. However, only about half of their study patients was screened and received prophylaxis appropriately.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that microbial invasion of the amniotic cavity with U. urealyticum is a risk factor for impending preterm delivery and adverse perinatal outcome [24]. Other pathogens associated with chorioamnionitis are Escherichia coli [49], Group B Streptococcus [23] and rarely Candida albicans [12]. Amniotic¯uid culture is an unreliable method for early diagnosis, detecting only 6±24% of patients with chorioamnionitis [39].…”
Section: Chorioamnionitismentioning
confidence: 99%
“…The woman often presents with fever, maternal tachycardia greater than 100 beats per minute, occasional chills, malaise, foul-smelling amniotic fluid (antepartum) or lochia (postpartum), and varying levels of uterine tenderness, although there may be no early localizing symptoms (Bernstein, 2000). Maternal leukocytosis greater than 15,000 cells/mm3 may be present, and the fetal heart rate is frequently tachycardic (Katz, Hibbard, Ranganathan, Meadows, & Ismail, 1999). A diagnosis of intraamniotic infection can be made when two or more symptoms are present together with an intrapartal temperature greater than 37.8"C (Katz et al, 1999).…”
Section: Pathologymentioning
confidence: 99%
“…Maternal leukocytosis greater than 15,000 cells/mm3 may be present, and the fetal heart rate is frequently tachycardic (Katz, Hibbard, Ranganathan, Meadows, & Ismail, 1999). A diagnosis of intraamniotic infection can be made when two or more symptoms are present together with an intrapartal temperature greater than 37.8"C (Katz et al, 1999).…”
Section: Pathologymentioning
confidence: 99%